Learning outcomes in undergraduate economics - Colonescu, Constantin (My University, 2024)
A debate has been ongoing for a long time on the value of a college degree, particularly in economics. Critics of undergraduate economics education question the content being taught and whether students retain anything after graduation. A cause of the frustration is often the lack of criteria for measuring learning and teaching effectiveness - the lack of good learning outcomes and a way of measuring learning beyond the grade point average (GPA). This chapter is an initiative to shed some light on the learning outcomes of the undergraduate economics program using MacEwan University as a case study. Issues to be explored include what economics students should learn, how to incorporate learning outcomes at the course level, how to determine the learning outcome content in students' course portfolios and an alternative measure to GPA.
Keywords: undergraduate economics; grade point average (GPA); MacEwan University; case study; learning outcome content